Impact of Food Rations and Supplements on Micronutrient Status by Trimester of Pregnancy: Cross-Sectional Studies in the Maela Refugee Camp in Thailand - Stuetz, Wolfgang (Nutrients, 2016)
Micronutrient fortified flour (MFF), supplementary food rations and micronutrient (MN) supplements may prevent deficiencies among pregnant women. Objectives of cross-sectional surveys in 2004 (n = 533) and 2006 (n = 515) were to assess the impact of new food rations (flour, oil) and supplements on MN status by trimester of pregnancy in the Maela refugee camp. Hemoglobin, iron status, zinc, retinol, β-carotene and tryptophan decreased, while α-/γ-tocopherol and 5-methyltetrahydrofolate (5-MTHF) increased from first to third trimester. In 2006, mean zinc and α-tocopherol for each trimester was significantly higher than in 2004. The weeks of supplemented thiamine and folic acid were positively correlated with thiamine diphosphate (TDP) and 5-MTHF, but not for ferrous sulfate as iron deficiency was observed in 38.5% of third-trimester women. Frequent consumption of fish paste and owning a garden or animal were associated with significantly higher iron status, retinol, β-carotene, and 5-MTHF. In conclusion, MFF and supplementary oil were most likely to explain improved zinc and α-tocopherol status, while thiamine and folate supplements ensured high TDP and 5-MTHF in late pregnancy. MN supplements, MN-rich staple food, small gardens, and programs to improve iron compliance are promising strategies to prevent MN deficiencies during pregnancy in vulnerable populations.